Hope for Africa s youth - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The youth essay competition launched by CTA in collaboration with the Africa Technology Policy Studies Network (ATPS) attracted nearly 50 entries from all over the continent and all of a consistently high standard...